On the seeding of periodic Equatorial Plasma Bubbles by gravity waves associated with tropical cyclone: A case study - Ajith, K. K.; Li, Guozhu; Tulasiram, S.; Yamamoto, M.; Hozumi, K.; Abadi, Prayitno; Xie, Haiyong (My University, 2020)
Understanding the day‐to‐day variability of equatorial plasma bubble (EPB) irregularities has been a major challenge for many decades that makes the deterministic prediction of EPBs remain elusive. In the present study, we report a case of intense and periodic EPBs observed during 8 and 9 April2013 by the 47‐MHz Equatorial Atmosphere Radar at Kototabang, Indonesia. The periodic EPBs separated by about 200–250 km were initiated before sunset. The presunset onset and development of these periodic EPBs were discussed in light of the gravity waves (GWs) excited in connection with the deep convection due to the tropical cyclone (TC) Victoria. The outgoing long‐wave radiation measurement by very high‐resolution radiometer (VHRR) on board Indian meteorological satellite Kalpana‐1 shows the occurrence of deep convective activity during these days. The presence of upward propagating GWs from the deep convective region associated with TC Victoria was confirmed using the GPS radio occultation (GPS‐RO) observations in the troposphere and stratosphere. The GW signatures at ionospheric altitudes were also observed from the Ionosonde observations over magnetic equator, and medium‐scale (~300 km) GWs were observed from the GPS‐TEC (Total Electron Content) data near to the magnetic equator and cyclone center. From the GW parameters observed from GPS‐TEC and GPS‐RO, we surmise that the secondary GWs generated by the dissipation of primary GWs associated with TC Victoria could have served as a seeding source on the generation of periodic EPBs during these two consecutive days.
Keywords: Equatorial plasma bubbles; EPBs